Professionalism Of Woman Resources In Sarah Blake's The Posmistress (2010): A Feminist Criticism - Parmawati, Reni; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph.D (2015)
The main aim of this study is to find how proffesionalism of woman recources in Sarah's Blake The Postmistress viewed from Feminist's perspective, and to analyze the novel based on its structural elements. by correlating its structural elements and social historical background of American in early twenty first century. This study uses qualitative method in which the data are taken from both primary and secondary data source in form of words, sentence and phrases. Primary data source is Sarah Blake The Postmistress meanwhile secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. In analyzing The Postmistress, the researcher uses feminist approach. The outcomes of this study are as follows: (1) Sarah Blake writes The Postmistress as the mirror of American society through the structural elements of the novel to reflects the social realities; (2) Sarah Blake wants to explain the professionalism does not consider gender in the American society in early of twenty first century through The Postmistress novel.